Aspects of Financial Law as regards the use of renewable energy in Poland in the context of conformity to constitutional principles for stable development - Rudnicki, Maciej (Studia Ecologiae et Bioethicae, 2006)
The article describes the use renewable sources of energy particularly with regard to National Energy Policy in order to achieve good ecological results, principally through the reduction of the use of Greenhouse gases.